Proglucagon-Derived Peptides Do Not Significantly Affect Acute Exocrine Pancreas in Rats. Issue 7 (August 2016) - Akalestou, Elina; Christakis, Ioannis; Solomou, Antonia M.; Minnion, James S.; Rutter, Guy A.; Bloom, Stephen R.
Abstract : Objectives: Reports have suggested a link between treatment with glucagon-like peptide 1 (GLP-1) analogs and an increased risk of pancreatitis. Oxyntomodulin, a dual agonist of both GLP-1 and glucagon receptors, is currently being investigated as a potential antiobesity therapy, but little is known about its pancreatic safety. The aim of the study was to investigate the acute effect of oxyntomodulin and other proglucagon-derived peptides on the rat exocrine pancreas. Methods: Glucagon-like peptide 1, oxyntomodulin, glucagon, and exendin-4 were infused into anesthetized rats to measure plasma amylase concentration changes. In addition, the effect of each peptide on both amylase release and proliferation in rat pancreatic acinar (AR42J) and primary isolated ductal cells was determined. Results: Plasma amylase did not increase postpeptide infusion, compared with vehicle and cholecystokinin; however, oxyntomodulin inhibited plasma amylase when coadministered with cholecystokinin. None of the peptides caused a significant increase in proliferation rate or amylase secretion from acinar and ductal cells. Conclusions: The investigated peptides do not have an acute effect on the exocrine pancreas with regard to proliferation and plasma amylase, when administered individually. Oxyntomodulin seems to be a potent inhibitor of amylase release, potentially making it a safer antiobesity agent regarding pancreatitis, compared with GLP-1 agonists.